Effect of Chicken Cage Fertilizer and Rice Husk Charcoal as a Planting Media on Growth and Production of Bean Plant: Pengaruh Pupuk Kandang Ayam dan Arang Sekam Padi Sebagai Media Tanam terhadap Pertumbuhan dan Produksi Tanaman Kacang-kacangan - Suprayitno, Didik; Sari, Risca Kurnia; Widyastuti, Diena (Procedia of Social Sciences and Humanities, 2022)
People's need for vegetables is increasing day by day. One type of vegetable that is in great demand by the public is chickpeas. The productivity of chickpeas in 2014 decreased, the decline was caused by various things, one of which was the decline in soil quality due to excessive use of inorganic fertilizers. One way to increase the productivity of chickpeas is to replace inorganic fertilizers with organic fertilizers. The purpose of this study was to determine the effect of chicken manure and rice husk charcoal as a planting medium on the growth and yield of chickpeas. Based on the results of research and data analysis, it was found that the combination of treatment of chicken manure (P2), combination of soil + chicken manure (P4), soil + husk charcoal + chicken manure (P6) and soil + husk charcoal (P5) had a significant effect. significant effect on the growth of bean plants. The use of chicken manure and rice husk charcoal has also been shown to be able to increase the production of chickpeas by 200-500 %.